On a new synonymy in genus Laemostenus concerning a species from Iran (Coleoptera, Carabidae, Sphodrini) - Wrase, David W.; Casale, Achille (Zootaxa, 2019)
In 2018 the authors A. Casale & D.W. Wrase described Laemostenus (Arabosphodrus) laserae as new for science from South Iran (Province of Hormozgan) in Annales de la Société entomologique de France (N.S.), 54 (4), 309-317. This paper was also published online on 31 July 2018 (datum already confirmed by ZooBank on 15 July 2018) (http://zoobank.org/urn:lsid:zoobank.org:pub:0962027A-E245-41B3-80F3-F8C32B8D3D44), and as printed copy in this international widespread journal with date of publication “May-July 2018“. The description was based on a long series of specimens collected in 2015.